Utilization of rice husk and poultry wastes for renewable energy potential in Pakistan: An economic perspective. (August 2016) - Ali, Ghaffar; Bashir, Muhammad Khalid; Ali, Hassan; Bashir, Muhammad Hamid
Abstract: The present work reports the potential of rice husk mixed with poultry waste as an alternative source to generate energy. The rice husk and poultry waste have substantial potential for the production of power and energy. The energy obtained from this process is renewable energy which is considered environment-friendly. Using this technology, the timber used as fuel in the power plants can also be saved from its depletion. The studies show that two types of benefits can be obtained from such technology that is power generation and cleanliness of the environment. Benefit gains in the first year are less due to the fixed installation cost of the biogas plant but afterwards the benefit gains are larger. The benefit-cost analysis shows that the installation of biogas plant using rice husk with poultry waste is feasible in Pakistan. In anaerobic fermentation process biogas is produced in the absence of oxygen. The by-products such as bio-slurry produced during the anaerobic fermentation process can be utilized as fertilizer to enhance the soil fertility and reduce the import bills of synthetic fertilizers. The generation of renewable energy by using rice husk and poultry waste is economically feasible, socially sound and environment-friendly.